2020
DOI: 10.1007/s40415-020-00601-y
|View full text |Cite
|
Sign up to set email alerts
|

Seed morphology and fatty acids composition among Flax populations

Abstract: Flax (Linum usitassimum L.) of family Linaceae is one of the most important crops, which has been widely used from ancient times. The aim of the study was to examine seed morphological characteristics and fatty acids differences among 13 populations of flax (11 from Iran, one from Turkey and one from USA). We studied six morphological variables of seeds in 50 replications. The methyl esters of seeds fatty acids were analyzed using GC. We detected that the flax seeds shape and color were stable among the popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Several studies have vastly investigated morphological and molecular genetic variability of important linseed traits in extensive world collections (Soto‐Cerda et al, 2013; You et al, 2017). However, depending on heritability, morpho‐phenological characteristics may differ among unlike populations of the same species under different ecological conditions (Talebi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have vastly investigated morphological and molecular genetic variability of important linseed traits in extensive world collections (Soto‐Cerda et al, 2013; You et al, 2017). However, depending on heritability, morpho‐phenological characteristics may differ among unlike populations of the same species under different ecological conditions (Talebi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A significant (p<0.05) negative correlation between FA10 and FA 5 (r=−0.72) might be due to the increase of one fatty acid leads to a corresponding decrease in the other 41) . The positive correlation (p<0.001) between the fatty acids composition such as FA17 (Palmitic acid methyl ester) with FA20 (Stearic acid methyl ester) can help breeders to select such populations for domestication and further breeding programme 24) . The differences in fatty acid compositions might be due to different phases of biosynthesis of those compounds and the accumulation of fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the genetic composition of plant 20) , variety, geographical locations, edaphic factors, climatic conditions, stage of fruit development, and their interaction are also known to influence the fatty acid composition 19,20) . Studies reported that fatty acids of Ocimum basilicum are affected by geographical and environmental variation 21) ; type of variety, climatic conditions, soil type and maturity difference in plant affect fatty acids of Mango 22) ; different geographic locations affect the fatty acids of Pinus pinea 23) ; Linum usitatissimum 24) , and Prunus sibirica 25) . However, such types of studies are lacking in P. utilis.…”
Section: Introductionmentioning
confidence: 99%
“…For clustering analyses of the evaluated cultivars, we standardized the quantitative data (mean = 0, variance = 1) and used for Principal Coordinate Ordination (PCO), Unweighted Paired Group using Average method (UPGMA) and Principal Correspondence Analysis (PCA) by MVSP according to Talebi et al (2020).…”
Section: Statistical Analysesmentioning
confidence: 99%